Dampak Status Gizi Terhadap Kejadian Dismenorea - Fauzia, Nura Suciati; Nuraida, Ida; Raharsari, Rezeki Tri; Putri, Devia Lydia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Dysmenorrhea is menstrual cramps or menstrual pain that occurs mainly in the lower abdomen, but can radiate to the lower back, waist, pelvis, upper thighs, to the calves. Dysmenorrhea or cramps during menstruation also affect a person's quality of life, so that it can result in absenteeism from school, and can affect a person's nutritional status. Analyzing the relationship between nutritional status and the degree of dysmenorrhea in students. This research was conducted using a cross sectional approach. As an approach as many as 112 female respondents. The research sample size was calculated using the Slovin formula, so that a total sample of 53 students was obtained and was selected as a sample using simple random sampling technique. Univariate and bivariate analysis was used in this study using the chi-square test. The results of the study illustrate that the nutritional status is 0.015 so it can concluded that the nutritional status variable and the dysmenorrhea variable have a significant relationship. From the results of the study, it is illustrated that there is a relationship between nutritional status and the incidence of dysmenorrhea in students.